Infectious Mimicry Complicates Diagnosis in Hemophagocytic Syndrome Caused by Anaplastic Large-Cell Lymphoma - Michael J. Peluso; David Chia; Whitney Sheen; Christoph Hutchinson; Lydia Barakat (Case Reports in Medicine)
Hemophagocytic syndrome (HPS) arises secondary to genetic, rheumatologic, neoplastic, and infectious causes. We discuss a patient whose presentation was consistent with systemic infection but was discovered to have HPS of unknown etiology. The presenting symptoms, as well as unremarkable malignancy and rheumatologic workups, led to the pursuit of an infectious cause, but the patient was ultimately discovered to have an occult anaplastic large-cell lymphoma (ALCL). This case demonstrates the diagnostic challenges that result from infectious mimicry in the context of HPS—first, in distinguishing noninfectious HPS from the systemic inflammation that can result from a widespread infectious process, second, in the identification of the precipitating cause of HPS. While evidence of these challenges has been suggested by the limited literature on HPS and ALCL, our case illustrates the diagnostic dilemma that arises when tissue biopsy does not quickly reveal an etiology. It is important that all physicians be aware that HPS can mimic infection and be prepared to redirect the workup when an infectious etiology for HPS cannot be identified.